The Use of Fair Value and Historical Cost Accounting for Investment Properties in China - Ross Taplin; Wei Yuan; Alistair Brown (Australasian Accounting, Business and Finance Journal, 2014)
This paper examines the use of fair value accounting for investment properties by 96 randomly selected Chinese listed companies’ year-ending 2008 annual reports. Half the sampled companies use fair value while half use historical cost, both methods being allowable under International Financial Reporting Standards (IFRS) and Chinese Accounting Standards (CAS). This represents the lowest possible level of comparability (or harmony) when there are only two choices of method. A combination of T indices to summarise the level of comparability and logistic regression reveals that companies with an international influence (listed on international stock exchanges and/or with international operations) are more likely to use fair value. Furthermore, there is evidence that companies with above average volatility in earnings are more likely to use fair value than historical cost. The consequences for domestic and international harmony for regulators and investors is discussed in the context of the opening of Chinese markets to international investment.
Keywords: fair value; investment properties; accounting policy choice; China